Unlocking Innovation in Coffee SMEs: The Transformative Power of Knowledge Sharing - Hermina, Tinneke (Jurnal Wacana Ekonomi, 2023)
This study investigates the impact of knowledge sharing on individual innovation capability within coffee Small and Medium Enterprises (SMEs) in Kab. Garut. Utilizing a quantitative research design, the study employs descriptive and associative approaches to analyze data collected via surveys and interviews. The findings, based on SPSS analysis of responses from coffee SME employees, confirm that knowledge sharing significantly enhances individual innovation capability. Specifically, the dimensions of knowledge collecting and donating were examined, with knowledge donating showing a more substantial positive influence. This research corroborates existing literature suggesting that effective knowledge management practices not only foster individual innovation but also enhance overall organizational performance. Recommendations include strengthening knowledge-sharing practices, enhancing technology training, encouraging proactive knowledge donation, and implementing comprehensive knowledge management systems. The study's outcomes suggest that fostering an environment rich in shared knowledge and skills is pivotal for sustaining innovation and competitiveness within SMEs.